Financial strain and electronic nicotine delivery systems use among U.S. young adults: A longitudinal panel analysis, 2013–2018. (March 2021) - Han, Dae-Hee; Seo, Dong-Chul
Highlights: The role of financial strain on ENDS use varies by levels of current ENDS use. Financial strain prospectively predicts non-daily ENDS use, but not daily use. Problem Behavior Theory helps understand the link between financial strain and ENDS. Abstract: Introduction: Financial strain is associated with an increased likelihood of cigarette smoking, but less is known about its association with electronic nicotine delivery systems (ENDS) use. This study examined longitudinal associations of financial strain with ENDS use behaviors among young adults. Methods: We analyzed in 2020 four waves (2013–2018) of the Population Assessment of Tobacco and Health, a nationally representative longitudinal study. A total of 5740 U.S. young adults (aged 18–24 years at baseline) had matched data for all four waves. We used generalized linear mixed modeling which accounts for correlations between repeated measures. Weighted logistic regressions assessed the association between financial strain and three different types of ENDS use behaviors (i.e., everyday, some-day, and experimental use), adjusting for major confounders including poverty, mental health symptoms, and other substance use behaviors. Results: Frequency and proportion of everyday ENDS use showed a linear increase over time whereas some-day and experimental uses showed quadratic trends, increasing with a peak at Wave 2 and then decreasing over time. Financial strain prospectively predicted some-day (adjusted odds ratio [AOR] = 1.32; 95% CI = 1.03–1.69) and experimental (AOR = 1.25; 95% CI = 1.02–1.52) ENDS use, but not everyday use. Conclusions: The findings of the current study indicate the need for distinctly different approaches for non-daily ENDS users from daily users. Our findings further suggest that ENDS use prevention and cessation efforts should consider financial strain of young adults particularly for non-daily users to thwart them from progressing towards nicotine dependence and long-term use.